Land Resources Management in Southeast Asia: Redefining the Role of Women as Land Managers - Pradipta, Lengga (Universitas Negeri Semarang, 2020)
The global trend to transform land management responsibility from the state to 'communities' or local user groups has neglected the implications of intra-community power differences for the effectiveness and equity of land management. Despite the rhetoric about gender equality that has mushroomed in recent years, a review of evidence from several countries in Southeast Asia, such as Malaysia, Indonesia and Vietnam, has shown that female participation is very minimal in land management. One basic reason for this is the formal and informal institutional exclusion of women. Moreover, the bargaining power of women within households and communities is categorized as 'lip-service' because patriarchy is seen as bonded to culture or tradition. Further detailed and comparative research is required to identify and analyze the major factors that affect women's access and control over land resources, especially regarding how culture and local wisdom can accommodate this issue and ensure the participation of women in the management of resources.